2012
DOI: 10.2166/wh.2012.190
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of human and swine adenovirus, human norovirus and swine circovirus in water samples in Santa Catarina, Brazil

Abstract: Animal and human wastewater can potentially contaminate water sources and the treatment of drinking water may not effectively remove all contaminants, especially viruses. The purpose of the present study was to evaluate the viral contamination of water used for human and animal consumption in the city of Concórdia, located in southern Brazil. Porcine circovirus type 2 (PCV2), porcine adenovirus (PAdV), human adenovirus (HAdV) and human norovirus (NoV) were searched for using quantitative polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
1
17
1
1
Order By: Relevance
“…In a similar study, Garcia et al (2012) detected human and animal virus in drinking water from a deep well in Concórdia City; however, lower values were detected when compared with the current study. This fact may signal the contamination increasing in Concórdia City groundwater.…”
Section: Real-time Qpcrcontrasting
confidence: 72%
“…In a similar study, Garcia et al (2012) detected human and animal virus in drinking water from a deep well in Concórdia City; however, lower values were detected when compared with the current study. This fact may signal the contamination increasing in Concórdia City groundwater.…”
Section: Real-time Qpcrcontrasting
confidence: 72%
“…Schneider et al (2009) isolated E. coli from Suruvi river (surface water) and wells located near the river (groundwater), and the results showed that from the 205 E. coli isolates, more than a half were resistant to antibiotics (63 % from groundwater and 52 % from surface water). Garcia et al (2012) evaluated water from Pinhal river (located about 20 km from the Suruvi river), and detected the presence of enteric viruses from human and swine origin; besides, Palhares et al (2014), also studying Pinhal river and applying the same isolation method as the present study, found Salmonella spp. resistant to more than 20 antimicrobials.…”
Section: Discussionmentioning
confidence: 77%
“…Em São Paulo, houve contaminação em 53,3% dos poços em área rural (Piranha e Pacheco, 2004) e 66,6% de contaminação em aquífero freático de um cemitério (Matos e Pacheco, 2002). Em trabalho realizado no estado de Santa Catarina, todos os poços analisados em uma área de produção suinícola apresentaram AdV humano e suíno (Garcia et al, 2012). No Estado do Rio Grande do Sul, no município de Tenente Portela, a presença de AdV na porção de confinamento do SAG demonstrou contaminação em 100% dos pontos amostrados em fazendas de produção leiteira (Spilki et al, 2013), podendo indicar contaminação proveniente das áreas de recarga do aquífero.…”
Section: Resultsunclassified